OPTIMIZING THE CONNECTION OF PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) WITH VOCATIONAL SOFT SKILLS DEVELOPMENT - Sanam, Sanam (Sanata Dharma University Yogyakarta, 2024)
The Projek Penguatan Profil Pelajar Pancasila (P5) as an educational innovation in the Merdeka Curriculum program offers a holistic approach to strengthening students' understanding of Pancasila values. On the other hand, vocationalization demands the development of practical skills and soft skills relevant to the world of work. The purpose of this study is to analyze the extent to which the implementation of P5 contributes to the development of students' vocational soft skills. The research method involved observations and interviews with students and educators at relevant vocational schools. The results showed a positive relationship between the P5 dimensions and vocational soft skill development, with significant improvements in skills such as teamwork, communication, and problem-solving. In conclusion, the integration of P5 in vocational programs can be an effective strategy to create students who are not only technically competent but also possess the soft skills necessary to succeed in the modern workforce.